2019
DOI: 10.3389/fimmu.2019.02224
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Duck STING in IFN-β Induction and Anti-H9N2 Avian Influenza Viruses Infections

Abstract: The stimulator of interferon genes (STING) protein has been shown to play a pivotal role in response to both cytosolic RNA and dsDNA to elicit interferon (IFN) production in mammals. However, the role of duck STING (DuSTING) in antiviral innate immunity, especially in anti-RNA virus infection, has yet to be elucidated. In this study, the function of DuSTING in IFN induction and its role in anti-RNA virus infections were studied. DuSTING was amplified via reverse transcription-polymerase chain reaction (RT-PCR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 30 publications
(49 reference statements)
0
17
0
Order By: Relevance
“…Duck STING (DuSTING) shares 43 and 71% identity to human and chicken STING (chSTING), respectively (Cheng et al, 2019a). DuSTING is most highly expressed in the glandular stomach, followed by the trachea, lung, small intestine, spleen, kidney, and bursa (Cheng et al, 2019a). ChSTING is most highly expressed in the thymus, bursa, spleen, lung, and intestine of uninfected chickens (Ran et al, 2018).…”
Section: Stingmentioning
confidence: 99%
“…Duck STING (DuSTING) shares 43 and 71% identity to human and chicken STING (chSTING), respectively (Cheng et al, 2019a). DuSTING is most highly expressed in the glandular stomach, followed by the trachea, lung, small intestine, spleen, kidney, and bursa (Cheng et al, 2019a). ChSTING is most highly expressed in the thymus, bursa, spleen, lung, and intestine of uninfected chickens (Ran et al, 2018).…”
Section: Stingmentioning
confidence: 99%
“…After 24 h, the lysates were immunoprecipitated with anti-HA beads, followed by immunoblotting analysis with the indicated Abs. to inhibit the replication of H9N2 AIV (22). In this study, we found that duTRIM32 directly interacts with duSTING and contributes to the production of IFN-β mediated by duSTING, though the increase level is <2-folds.…”
Section: Discussionmentioning
confidence: 64%
“…Several TRIM proteins, including TRIM29, TRIM30α, TRIM32, and TRIM56 have been reported to regulate the mammalian STING-mediated pathways (11,19,20). DuSTING was reported to activate the type I IFN pathway and exhibited antiviral effects against both DNA and RNA viruses (21,22). However, whether duTRIM32 regulates the duSTING-mediated pathway remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, STING overexpression led to significant activation of NFκB, IFN-β, and ISRE promoter elements along with an antiviral effect towards DPV infection [176]. Another study reported the antiviral effect of overexpressed STING against H9N2 LPAI virus infection in DEFs [177]. Lastly, DTMUV NS2B3 protease was demonstrated to cleave STING and abrogate downstream signaling to TBK1 signifying virus-encoded evasion mechanisms to subvert IFN induction [178].…”
Section: Stingmentioning
confidence: 96%